Identification of multiple rare earths and associated elements in raw monazite sands by laser-induced breakdown spectroscopy - Abedin, K.M.; Haider, A F M Yusuf; Rony, M.A.; Khan, Z.H. (© 2010 Elsevier Ltd., 2017)
This article was published in the Journal Optics and Laser Technology [© 2010 Elsevier Ltd.] and the definite version is available at : 10.1016/j.optlastec.2010.05.003